The Challenges of Anthropology in the Arab Gulf: Few Reflections on the Omani Case - Sebiane, Maho (Social Anthropology in the Arab World: The Fragmented History of an Uncomfortable Discipline, 2025)
"There are ongoing efforts in anthropology to decolonise its history and give fairer space to marginalised traditions. This book examines the history and institutionalisation of anthropology in the Maghreb, the Mashreq and the Gulf, in an open and collaborative manner and from various perspectives. Its primary focus is two-fold: first, to reorient the anthropological focus towards studies conducted in the region, particularly on the conditions conducive to the institutionalisation of anthropological knowledge; second, to shed light on anthropological studies in languages other than English offering different theoretical and epistemological perspectives"-- Provided by publisher.
Keywords: Moeurs et coutumes -- Oman

داون شاتي وماندانا لمبرت والدراسات الأنثروبولوجية في سلطنة عمان - علي, عثمان محمد عثمان; سعود, الطاهر (عمران للعلوم الإجتماعية و الإنسانية, 2024)
This paper investigates the anthropological research on Omani society, represented by a package of studies conducted by two American anthropologists: Dawn Chatty and Mandana Lambert. Working on these studies allows us to trace certain characteristics of the American anthropological research focused on the Global South, and on the Middle East in particular. These studies followed an anthropological approach that is usually devoted to culture and practical issues in areas like health, administration, and economic development. They date back to the 1990s and reflect the moment in which they were written and the interests of the two researchers in the phenomena that caught their attention. Therefore, the topics pursued were prevalent in a society undergoing transformation or on the path to development following the ascent of Sultan Qaboos bin Said to the throne in 1970.
Keywords: Moeurs et coutumes -- Oman

Healing, performance and gender: communities of practice in the Batinah Coast of Oman - Ismail, Hanadi (Seminar for Arabian Studies, 2012)
Keywords: Moeurs et coutumes -- Oman

Oman, a village - Eickelman, Dale F. (Saudi Aramco World, 1983)
Keywords: Moeurs et coutumes -- Oman

Of ties and time: Sociality, gender and modernity in an Omani town - Limbert, Mandana E. (University of Michigan, 2002)
This dissertation is about a town in Southern Arabia and the ways that gendered sociality and infrastructural transformation meet and become mediated through peoples' understandings of local history and religious values. Focusing on the mundane social world of neighborhood women in the town of Bahla in the oil-rich state of the Sultanate of Oman, I analyze how memories and interpretations of urban life play out in relation to people and practices understood to be at the margins of shifts that have come to define a town's contemporary history. The subjects of this dissertation are housewives, divorcees and widows who inhabit the town through their daily visiting, exchanges and stories. Their activities and conversations demonstrate unintended effects and re-workings of development projects, discourses and policies, as well as multiple, subtle and contradictory ways that the past is entangled in daily lives. Each chapter of this dissertation is structured along two intersecting axes. On the one hand, I focus on the material structures and technologies that Bahlawis associate with development and modernity, and, on the other, I examine related aspects of the mundane social world of women. Tacking back and forth between the two allows me both to investigate the materiality of abstract notions such as development and modernity, and to provide an account of the mundane and quotidian. Examining the material incarnations of development, such as settlement patterns and roads, plastic thermoses, abundant coffee, schools and piped water entangled in women's daily encounters, as well as discourses (including religious) surrounding these icons of development illustrates the complex ways they are helping to shape and being shaped by gendered sociality. Bringing these two axes together highlights how gendered sociality is not only, as numerous studies on women's networks have illustrated, a site in which one can observe social organization or mechanisms of solidarity and hierarchy. This dissertation argues that the configurations of sociality are also historically contingent as well as objects of shifting discourses, notions and practices of development, domesticity, heritage, history and religion.
Keywords: Moeurs et coutumes -- Oman

In the ruins of Bahla: reconstructed forts and crumbling walls in an Omani town - Limbert, Mandana E. (Social Text, 2008)
Keywords: Moeurs et coutumes -- Oman

The sacred date: gifts of God in an Omani town - Limbert, Mandana E. (Ethnos, 2008)
Keywords: Moeurs et coutumes -- Oman

al-ʿĀdāt wa’l-Taqālīd fī Wilāyat Samā’il - Hāshimī, Sulaymān b. Sayf al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Moeurs et coutumes -- Oman

al-ʿĀdāt wa’l-Taqālīd wa-mā yartabiṭu bihā min ʿAlā’iq Ijtimāʿiyya (Dirāsa Maydāniyya) - Musallimiyya, Shaykha bint Sālim (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Moeurs et coutumes -- Oman

al-Mawrūth al-Shaʿbī fī Wilāyat al-Muḍaybī - Hāshimī, Saʿīd b. Muḥammad b. Saʿīd al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Moeurs et coutumes -- Oman

al-Mawrūth al-Shaʿbī li-Wilāyat Mirbāṭ - Bālkhayr, Aḥmad b. ʿAbd al-Raḥmān (Mirbāṭ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Mirbāṭ Yawm al-ithnayn wa’l-thulathā’ 27-28 Shawwāl 1432 H. al-muwāfiq 26-27 Sibtimbar 2011, 2012)
Keywords: Moeurs et coutumes -- Oman

al-ʿĀdāt wa’l-Taqālīd al-Mushtaraka bayna ‘l-Mujtamaʿ al-ʿUmānī wa’l-Maghribī fī ‘l-Tārīkh al-Muʿāṣir: Muqāraba Tārīkhiyya - Būtshīsh, Ibrāhīm al-Qādirī (Aʿmāl al-Mu’tamar al-ʿIlmī al-thālith ḥawla ‘l-Taḥawwulāt fī ‘l-Mujtamaʿ al-ʿUmānī al-Ḥadīth wa’l-Muʿāṣir, 2005)
Keywords: Moeurs et coutumes -- Oman

al-Mawrūth al-Shaʿbī fī Wilāyat Ibrā’ (al-Fulklūr) - Hāshimī, Saʿīd b. Muḥammad b. Saʿīd al- (Ibrā’ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Ibrā’ Yawmay al-Ithnayn wa’l-Thulāthā’ 23-24 Shaʿbān 1423/8-9 Dec. 2003, 2007)
Keywords: Moeurs et coutumes -- Oman

La société rurale omanaise - Le Cour Grandmaison, Colette (La Péninsule arabique d'aujourd'hui, 1982)
Keywords: Moeurs et coutumes -- Oman

min Muʿjam Alfāẓ al-Ḥayāt fī Salṭanat ʿUmān. Dirāsa wa-Taḥlīl - ʿAmāyira, Ḥalīma (Aʿmāl al-Multaqà al-ʿIlmi al-awwal ḥawla Turāth Salṭanat ʿUmān al-Shaqīqa Qadīman wa-Ḥadīthan, 2002)
Keywords: Moeurs et coutumes -- Oman

Religiosity, Men of Learning, and Oil Wealth in the Land of the Imamate - Limbert, Mandana E. (Knowledge, Authority and Change in Islamic Societies, 2021)
Keywords: Moeurs et coutumes -- Oman

The Arabs of Oman - Storm, W. Harold; Harrison, Paul W. (The Muslim World, 1934)
Keywords: Moeurs et coutumes -- Oman